2009
DOI: 10.3844/ajptsp.2009.136.143
|View full text |Cite
|
Sign up to set email alerts
|

Camel’s Milk Protects Against Cadmium Chloride-Induced Hypocromic Microcytic Anemia and Oxidative Stress in Red Blood Cells of White Albino Rats

Abstract: Problem statement: Cadmium is a heavy metal of wide occupational and environmental contamination. In recent years, however, Cadmium has been implicated in the pathogenesis of several clinical disorders. One of the most frequently described problems in aluminum toxicity is anemia. Therefore, the present study was carried out to determine the effectiveness of Camel's milk in alleviating the toxicity of Aluminum Chloride (AlCl 3 ) on certain hematological parameters and antioxidant system components in the RBC's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
4
22
0
Order By: Relevance
“…It was well known that anemia reduces the supply of oxygen to tissues by lowering the oxygen-carrying capacity of the blood. This finding is consistent with previous studies of anemia in rodents exposed to Cd [38]. The present study showed that toxic effects of Cd leads to decreased hemoglobin, hematocrit, and M.C.V.…”
Section: Discussionsupporting
confidence: 94%
“…It was well known that anemia reduces the supply of oxygen to tissues by lowering the oxygen-carrying capacity of the blood. This finding is consistent with previous studies of anemia in rodents exposed to Cd [38]. The present study showed that toxic effects of Cd leads to decreased hemoglobin, hematocrit, and M.C.V.…”
Section: Discussionsupporting
confidence: 94%
“…Many studies about detoxification of water and food by utilization of different microorganisms are available (Haltttunen et al, 2006(Haltttunen et al, , 2007Fandi et al, 2006). Many experiences were done with laboratory animals to study lead distribution in vivo by treating orally, inhalation or injection (Dallak, 2009;Castellino and Aloij, 1969;Rader et al, 1981;Smith et al, 1992). But, there are no many studies about interaction of LAB and heavy metals in vivo and influence for retention or elimination of Pb.…”
Section: Quantity Of Lead In Faecesmentioning
confidence: 99%
“…This situation should have various adverse effects on a human body (Tuhvatshin et al, 2008). The pollution by lead (Pb) is a health hazard for consumers of dairy products because this metal is concentrated throughout the food chain (Tajkarimi et al, 2007;Dallak, 2009;Kan and Meijer, 2007). High level of lead was observed in the blood samples of individuals inhabiting the polluted areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood cells were determined using an aperture-impedance method (Dallak, 2009) by an automatic blood cell analyzer (PE-6800 Vet, Electronica Co., Ltd. Shenzhen Pukang, China). When a diluted sample including blood cell is injected into the aperture, the change of electrical resistance due to the passing blood cells can be estimated approximately.…”
Section: Analysis Of Blood Routine and Metabolitesmentioning
confidence: 99%